Budd–Chiari syndrome secondary to caudal vena cava obstruction by vascularly invasive lymphoma in a cat. Issue 2 (11th February 2022) - Whitlock, James; Alexander, Akash; Williams, Claire; Griffin, Sally; Allerton, Fergus
Abstract: A 2‐year‐old female neutered domestic shorthair cat presented with ascites following a 2‐week history of hyporexia and moderate weight loss. Sonographic assessment of the abdominal cavity identified a hepatic mass in close association with the caudal vena cava that contained an intraluminal structure. Computed tomography confirmed the hepatic mass in the right craniodorsal aspect of the liver with invasion of the posthepatic caudal vena cava and consequent vessel occlusion. This congestion caused transudation of fluid from the vasculature, resulting in the observed ascites (Budd–Chiari syndrome). Cytology from fine‐needle aspirates of the mass confirmed a diagnosis of high‐grade lymphoma. The patient was started on a high‐dose COP chemotherapy protocol, consisting of cyclophosphamide, vincristine and prednisolone. The patient showed a dramatic improvement in its clinical signs, with resolution of the ascites within 1 week of starting treatment. After a 12‐month period, chemotherapy was stopped, and 2.5 years after first diagnosis the patient has excellent quality of life with no current health problems related to its atypical lymphoma presentation.